2022
DOI: 10.3390/ijerph19095162
|View full text |Cite
|
Sign up to set email alerts
|

You Really Affect Me: The Role of Social Influence in the Relationship between Procedural Justice and Turnover Intention

Abstract: This research aims to test the impact of procedural justice on employees’ turnover intention via their intention to stay or give up their positions by putting social influence in the spotlight as a mediating variable. Although the topic dealing with the relationship linking organizational justice to turnover intention has taken some wrinkles, there has been no published research, to the best of researchers’ knowledge, that integrates social influence as a mediating variable between the aforementioned relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 76 publications
0
18
1
Order By: Relevance
“…The results from the analysis indicated that three aspects of justice (distributive, procedural, and interpersonal) significantly and positively influenced turnover intention. These findings do not agree with our hypotheses and are inconsistent with most past research studies, where distributive justice ( Akgunduz and Cin, 2015 ; Yang et al, 2021 ; Chen et al, 2022 ), procedural justice ( Kumar, 2015 ; Gharbi et al, 2022 ), and interpersonal justice ( Leineweber et al, 2020 ) were mainly observed to affect turnover intention negatively.…”
Section: Discussioncontrasting
confidence: 99%
“…The results from the analysis indicated that three aspects of justice (distributive, procedural, and interpersonal) significantly and positively influenced turnover intention. These findings do not agree with our hypotheses and are inconsistent with most past research studies, where distributive justice ( Akgunduz and Cin, 2015 ; Yang et al, 2021 ; Chen et al, 2022 ), procedural justice ( Kumar, 2015 ; Gharbi et al, 2022 ), and interpersonal justice ( Leineweber et al, 2020 ) were mainly observed to affect turnover intention negatively.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite this unethical behaviour, however, could benefit the organisation in the short term, it will have a negative influence on the organisation in the long term [ 7 , 9 ]. Additionally, the occurrence of this behaviour will defiantly affect the behaviour of other employees [ 34 ], which could spread this UPoB among all employees.…”
Section: Discussionmentioning
confidence: 99%
“…Turnover intention refers to the probability of an employee quitting his/her current job. Several predictors were identified for the turnover intention in hotels, including job insecurity [ 4 ] organizational justice in general [ 33 ], procedural justice [ 34 ] and distributive justice [ 4 ] in particular, sexual harassment and trust in superior [ 35 ], leadership style and organizational commitment [ 36 ], job satisfaction [ 37 ]. On the other side, turnover intention can r influence job performance [ 38 ] and the spread of deviant behaviour as well as social loafing behaviour [ 4 ].…”
Section: Hypothesis Development and Conceptual Frameworkmentioning
confidence: 99%
“…If employees perceive unequal procedures, they could respond with a negative attitude, such as exhibiting turnover intention and social loafing behavior. In that sense, previous studies (e.g., Aliedan et al 2022;Alyahya et al 2021;Sobaih et al 2019) argued that an intention to leave is usually associated with negative outcomes, such as low job-performance levels, unethical behavior and social loafing, while pervious research results (e.g., Griffeth et al 2000;Chong et al 2021;Gharbi et al 2022) confirmed that procedural justice is a key driver for employee turnover. Additionally, it was argued that procedural justice is more important than distributive justice in determining employees' evaluations of the parties or the institution that enacted the decision (Brockner and Siegel 1996).…”
Section: Introductionmentioning
confidence: 86%